Measures for the prevention of COVID-19 transmission for prehospital care workers - Moema Santos Souza; Marina Aparecida Chrispim Silva; Doane Martins da Silva; Larissa Viana Almeida Lieberenz; Mariana Almeida Maia; Marília Alves (Universidade Federal do Ceará, 2021)
Objective: to identify measures to prevent transmission of COVID-19 for prehospital care health care workers. Methods: integrative review using LILACS and BDENF databases via the Virtual Health Library, CINAHL, MEDLINE/PubMed, Web of Science, EMBASE, Cochrane Library, and SCOPUS. Results: eight publications were included that presented recommendations regarding the use of safety equipment by healthcare professionals and ambulance drivers and measures to prevent the risk of infection during invasive airborne procedures in suspected or contaminated COVID-19 patients. Conclusion: the preventive measures directed to prehospital care professionals were proper use of personal protective equipment and changes in the management of suspected/contaminated patients by COVID-19 and in invasive procedures or transportation of these patients. In addition, it is essential the cleaning and disinfection of the ambulances and their equipment.